Muslim childhoods in South Africa: gendering the madrasah space - Patel, Nafisa (Department of Religious Studies, 2022)
My thesis explores the spatialities and gendered pedagogies of Muslim childhoods within the context of selected South African madrasahs (places for religious instruction). The main question that guides my research study is how is the madrasah space gendered? Beginning with the assumption that madrasah spaces are gendered, my research seeks to understand Muslim childhoods and gender as a relational and materially contingent social phenomenon. I engage my research question with theoretical lenses developed by critical posthumanist and feminist educational thinkers focusing on the concepts of diffraction, entanglement and intra-action. These theoretical and analytical tools provide a lens for thinking about childhoods, gender and childhood pedagogies as ontologically relational. Diffraction attends to the multiplicity of interdependencies and ecological networks that constitute and shape interactions between subjects and objects. In this ontological-epistemological framework, the material, discursive and affective factors of social phenomena are seen as entangled and co-emergent encounters. My diffractive analysis is a place-attuned, relational reading of childhood ontologies, it focuses on the intra-actions between humans and more-than humans, nature-culture, organic-inorganic, and maps patterns of material-discursive affective entanglements. Using data co-generated from fieldwork observational studies conducted at four madrasah sites in the Western Cape, I diffractively analyse the spatialities and gendered pedagogies of Muslim childhoods. I map how historical geographical-political-social-pedagogical factors intra-act and participate in the gendering of space. My diffractive reading on Muslim childhood spatialities, in the final analysis, offers a lens for thinking about gendered ontologies in ways that are nonlinear, co-emergent and relational. This place-based perspective on madrasah pedagogies contributes to a broader conversation on religious geographies within a post-anthropocene context of environmental precarity, socio-economic inequalities and spatial disparities in South Africa.